Development of an ultra-small biomass gasification and power generation system: Part 2. Gasification characteristics of carbonized pellets/briquettes in a pilot-scale updraft fixed bed gasifier. (15th May 2018) - Ding, Lu; Yoshikawa, Kunio; Fukuhara, Minoru; Kowata, Yuto; Nakamura, Shunsuke; Xin, Dai; Muhan, Li
Highlights: The first study on carbonized pellets/briquettes in a pilot scale updraft gasifier. Inorganic Cl could be absorbed and changed to organic Cl bonded with carbon matrix. Carbonized pellets show a better performance than carbonized briquettes. The overall efficiency of the gas engine was evaluated. Abstract: Ultra-small biomass gasification and power generation systems are a promising technology for disaster areas in developed countries and non-electrified rural areas of developing countries. The gasification characteristics of carbonized wood pellets and carbonized wood briquettes without or with 1 wt% sea salt were tested in a pilot-scale updraft fixed-bed gasifier. The results showed that the carbon balance during gasification was easily achieved, and most of the chlorine in the carbonized briquettes with sea salt remained in the residual char and fly ash after gasification. Inorganic chlorine in the solid fuel was transformed into organic chlorine combined with carbon matrix after heat treatment in the gasifier. Syngas with a low heating value higher than 4 MJ·m −3 could be continuously obtained when the system reached a stable condition, which enabled power generation using a gas engine. A combination of several secondary tar removal processes was adopted for the syngas purification. The tar content in the syngas after the gas cleaning for 425 °C-carbonized pellet, 425 °C-carbonized briquette, 475 °C-carbonized briquette, and 475 °C-carbonized briquette with sea salt was 0.98, 0.26, 1.4, and 0.2 g·Nm −3, respectively. During the stable stage, 425 °C-carbonized pellet showed the highest cold gas efficiency (CGE) of 45.6% and carbon conversion efficiency (CCE) of 57.8%, respectively, with an equivalence ratio (ER) of 0.24. A lower carbonization temperature showed a higher CGE and CCE. The residual char and fly ash after gasification could be considered for reuse as feedstock to further improve the overall process efficiency. The maximum output power was 23 kW at an air flow rate of 40 Nm 3 /h during the gasification of carbonized pellets, and the corresponding overall power generation efficiency of the engine using the syngas was about 27.8%. For 475 °C carbonized briquette, the maximum output power was 18 kW at an air flow rate of 40 Nm 3 /h, and the corresponding overall power generation efficiency of the engine using the syngas was about 25.5%.